PENGARUH ETOS KERJA ISLAM, MOTIVASI DAN KOMPENSASI TERHADAP PRODUKTIVITAS DENGAN PRESEPSI KEMUDAHAN SEBAGAI VARIABEL MODERASI - Ikhlashul Amal Firdaus; Saiful Anwar (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to determine the influence of Islamic Work Ethic, Motivation and Compensation on productivity with the perception of convenience as a moderation variable. The object of research is part of SheopeeFood drivers in Semarang area. The sampling technique uses purposive sampling and data collection using questionnaires from 100 respondents. The analysis tool used is moderated regression analysis. The results of the study concluded that Islamic work ethic has a positive and significant effect on productivity, motivation has a positive and significant effect on productivity. Compensation has a positive and significant effect on productivity. The perception of convenience is able to moderate the influence of Islamic work ethic, motivation, compensation on productivity